Grain size distribution, clay mineralogy and chemistry of bottom sediments from the outer Thermaikos Gulf, Aegean Sea, Greece - PEHLIVANOGLOU, K.G.; TRONTSIOS, G.; TSIRAMBIDES, A. (Mediterranean Marine Science, 2004)
The Thermaikos Gulf constitutes the NW part of the North Aegean Sea and is limited eastward from the Chalkidiki Peninsula and westward from the Pieria Prefecture. Its plateau covers an area of 3,500 km2. The mechanisms responsible for the grain size distribution into the Gulf, the clay mineralogy and the chemistry of some bottom sediments from the outer Thermaikos Gulf, are examined. Source mixing during transportation, flocculation, differential settling processes and organic matter appear to be the main mechanisms for the distribution of clay minerals in shallow waters. All grain size fractions studied present a wide range of values confirming the extreme variations of the discharged load and the variability in marine processes. Plagioclases predominate over K-feldspars, while quartz is the most abundant mineral present. In addition, micas, chlorites, amphiboles and pyroxenes exist as primary and/or accessory minerals in all samples. Among clay minerals, illite predominates over smectite and smectite over chlorite (+ kaolinite). The ordered interstratified phase of I/S, with 30-35% S layers, is present in the 2-0.25µm fraction. The randomly interstratified phase of I/S, with 50% S layers, is present in the <0.25& micro; m fraction. On average the clay mineral content of the studied samples is: 48% I, 23% S, 17% Ch (+K) and 12% others for the 2-0.25µm fraction and 50% I, 30% S and 20% Ch (+K) for the <0.25 µm fraction. All these minerals are the weathering products of the rocks from the drainage basins of the rivers flowing into the Gulf, as well as of the Neogene and Quaternary unconsolidated sediments of the surrounding coasts. The terrigenous input, the water mass circulation and, to a lesser extent, the quality of the discharged material and the differential settling of grains, control the grain size distribution within the outer Thermaikos Gulf. The chemical composition of the analysed samples is generally in agreement with their mineral composition and signifies their terrigenous origin presenting discretely clastic character.